Transformasi Filantropi melalui Marketplace di Era Pandemi Covid-19 - Khotimah, Khusnul; Bakroni, Ahmad; Puspitasari, Neneng (STAINI Press, 2023)
In the current pandemic era, innovations related to the ziswaf payment model are urgently needed, in era 4.0 the digital role has reached all levels of society, besides that digital is also a way to reduce physical contact between individuals. Thi s research is descriptive research with a qualitative approach. This paper describes the fundraising approach in the digital era. The innovation of zakat institutions in fundraising is carried out in collaboration with marketplaces 1. Bukalapak, 2. Shope, 3. Tokopedia, 4. Lazada and 5. Blibi. The results of this study found that the five marketplaces combine business techniques with social business through philanthropy. This fusion of business commercial and social business shows the marketplace's concern for philanthropy. In the use of fundraising, each zakat institution and social institution applies different approaches, according to the characteristics of the offering model made by the marketplace.